EIT image regularization by a new Multi-Objective Simulated Annealing algorithm - Martins, Thiago Castro; Sales Guerra Tsuzuki, Marcos (2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2015)
Multi-Objective Optimization can be used to produce regularized Electrical Impedance Tomography (EIT) images where the weight of the regularization term is not known a priori. This paper proposes a novel Multi-Objective Optimization algorithm based on Simulated Annealing tailored for EIT image reconstruction. Images are reconstructed from experimental data and compared with images from other Multi and Single Objective optimization methods. A significant performance enhancement from traditional techniques can be inferred from the results.